Pengaruh Terapi Antituberkulosis Fase Intensif Terhadap Status Gizi Penderita Tuberkulosis Anak di RSUP Haji Adam Malik Medan Tahun 2018 - Fadila, Yuriza; Meirina, Fathia (Talenta Publisher, 2021)
Background: Tuberculosis (TB) is one of the 10 main causes of death from infectious diseases. Indonesia is among the 3 countries with the highest TB incidence in the world. The proportion of pediatric TB patients in North Sumatra Province is 2%. Antituberculosis therapy is a treatment used in TB patients. Successful diagnosis and treatment can prevent millions of deaths each year. Low endurance and malnutrition are factors that influence the possibility of someone becoming a TB patient. This situation can disrupt growth in children. Child growth can be monitored through nutritional status assessments. Objectives: This study aims to determine the effect of intensive phase antituberculosis therapy on the nutritional status of children with tuberculosis in Haji Adam Malik General Hospital Medan in 2018. Methods: This study uses an observational analytic method using a retrospective cohort design, using secondary data derived from medical records at Haji Adam Malik General Hospital Medan in 2018. Data obtained will then be processed and analyzed by the Wilcoxon test using a data processing program. The Wilcoxon test had a significant result (p = 0.001). Results: The mean increase in nutritional status after being given antituberculosis therapy in the age group of children 0-1 years and >1-5 years is a good nutritional status. The mean weight gain after being given antituberculosis therapy in the age group of children 0-1 years was 7.81 kg and >1-5 years was 15.32 kg. The pattern of a child's weight gain after reaching antituberculosis during the intensive phase has increased. Conclusion: In this study, it was found that antituberculosis therapy affected the nutritional status of children with tuberculosis during the intensive phase. Keywords: antituberculosis therapy, child growth, childhood TB, infectious disease Â Latar Belakang: Tuberkulosis (TB) merupakan salah satu dari 10 penyebab utama kematian dari golongan penyakit infeksi. Indonesia termasuk 3 negara dengan angka kejadian TB tertinggi di dunia. Proporsi pasien TB anak di Provinsi Sumatera Utara sebesar 2%. Terapi OAT merupakan tatalaksana yang digunakan pada pasien TB. Diagnosis dan pengobatan yang berhasil dapat mencegah jutaan kematian setiap tahunnya. Daya tahan tubuh yang rendah dan malnutrisi merupakan faktor yang mempengaruhi kemungkinan seseorang menjadi pasien TB. Keadaan ini dapat menyebabkan terganggunya pertumbuhan pada anak. Pertumbuhan anak dapat dipantau melalui penilaian status gizi. Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh terapi antituberkulosis fase intensif terhadap status gizi penderita tuberkulosis anak di RSUP Haji Adam Malik Medan tahun 2018. Metode: Penelitian ini menggunakan metode analitik observasional dengan menggunakan desain kohort retrospektif, menggunakan data sekunder yang berasal dari rekam medik di RSUP Haji Adam Malik Medan tahun 2018. Data yang diperoleh selanjutnya akan diolah dan dianalisis dengan uji Wilcoxon menggunakan program pengolahan data. Uji Wilcoxon memiliki hasil yang signifikan (p = 0,001). Hasil: Rerata peningkatan status gizi setelah diberikan terapi antituberkulosis pada kelompok usia anak 0-1 tahun dan > 1-5 tahun adalah berstatus gizi baik. Rerata peningkatan berat badan setelah diberikan terapi antituberkulosis pada kelompok usia anak 0-1 tahun adalah 7,81 kg dan > 1-5 tahun adalah 15,32 kg. Pola kenaikan berat badan anak setelah terapi antituberkulosis selama fase intensif mengalami peningkatan. Kesimpulan: Pada penelitian ini didapatkan bahwa terapi antituberkulosis berpengaruh terhadap status gizi anak penderita tuberkulosis selama fase intensif. Kata Kunci: penyakit infeksi, pertumbuhan anak, TB anak, terapi OAT